Press Briefings in International Climate Change Negotiations. Issue 5 (2nd September 2016) - Betzold, Carola; Bernauer, Thomas; Koubi, Vally
Abstract : Press conferences are an important element of a government's communication strategy at climate change summits. From a theoretical perspective, press conferences should serve two main functions: exerting pressure in negotiations and informing the public. These functions correspond to two logics of action: a logic of consequence where governments use press conferences as negotiation tools and a logic of appropriateness where governments organize press conferences to increase transparency. Based on new data from the United Nations Framework Convention on Climate Change archives, we find limited support for these two logics of action. Neither democracies, which, we argue, are more likely to follow a logic of appropriateness, nor vulnerable countries, which are more likely to follow a logic of consequence, organize systematically more press conferences. Other factors, such as capacity and a government's function in the negotiation structure, seem to play a more important role.